Complex impedance analysis of soft chemical synthesized NZCF systems - Parajuli, D.; Kumar Vagolu, Venkata; Chandramoli, K.; Murali, N.; Raj Sharma, Bhumi; Lal Shah, Nunu; Samatha, K. (Himalayan Physics, 2023)
The soft chemical method was adopted to prepare of cobalt-substituted nickel-zinc ferrites (Ni0.95-x Zn0.05COx Fe2O4 for x = 0.01, 0.02 and 0.03). We have recently studied their structural, morphological, and magnetic properties, initial permeability, and dielectric constant. They were found to be with cubic ferromagnetic spinel structure, the morphology of which is suitable for high-density recording media. The impedance has a major role in characterizing the electrical and magnetic properties of the sample, which are dependent on their permeability and dielectric constant. So, this study will verify the values obtained before. Next, the energy stored in a capacitor is directly proportional, and its size is inversely proportional to the dielectric constant. Similarly, the resistance offered by a material to the magnetic field to pass through it is related to permeability. This study will focus on the variation of impedance with Co2+ concentration. The results were derived with the equivalent circuit model. The impedance analysis is also important in the biological field having a name of Bio-Impedance Analysis (BIA), for determining nutritional status, and many more.